Cultivable Bacterial Diversity in the Gut of the Chagas Disease Vector Triatoma dimidiata: Identification of Possible Bacterial Candidates for a Paratransgenesis Approach - Lopez-Ordonez, Teresa; Flores-López, Carlos A.; Montejo-Lopez, Rene; Cruz-Hernandez, Andres; Conners, Erin E. (Frontiers in Ecology and Evolution, 2018)
Since bacterial symbionts play a vital role in the metabolism of hematophagous insect vectors the method known as paratrangenesis, which consists of the use of cultivable insect symbionts to interfere with the transmission of vector-transmitted pathogens has been shown to be effective in certain vector control oriented studies. In Chagas disease research a recent study introduced transgenes through a parastransgenic approach and prevented the development of a vector species for this disease. However this approach requires a previous characterization of the bacterial symbionts present in the species vector of interest, since a selection of the cultivable bacterial symbiont used is mandatory. In this study, we describe the gut bacterial diversity of Triatoma dimidiata specimens from Southern Mexico. Bacteria from both wild and laboratory-reared specimens were cultured, and resulting colonies were grown individually, harvested, and subsequently identified by 16S ribosomal loci sequencing. A total of five and three genera and a total of nine and six bacterial species were identified from field captured and laboratory reared Triatoma dimidiata specimens respectively. A majority of Gram positive bacteria were identified, which included the genera Staphylococcus, Bacillus, Brevibacterium, Micrococcus and Delftia. Given previous studies we propose the use of Staphylococcus saprophyticus, Micrococcus luteus and Bacillus megaterium as potential candidates for future paratransgenic efforts done with Triatoma dimidiata, which is one of the most important vectors of Chagas disease, in Central and South America. Given the vital association bacterial symbionts play in the metabolism of routes of hematophagous insect vectors Paratransgenesis consists of the use of cultivable insect symbionts to interfere with the transmission of vector-transmitted pathogens.